A Computer Program for Solving LP Problems by 2-Basic Variables Replacement at Each Simplex Iteration - Hasan, M Babul; Asaduzzaman, SM (Dhaka University Journal of Science, 2013)
In this paper, we develop a computer technique to implement the existing 2-basic variable replacement method of Paranjape for solving linear programming (LP) problems. To our knowledge there is no such computer oriented program which implemented Paranjapes method. Our computer oriented program is a faster method for solving linear programs. A number of numerical examples are illustrated to demonstrate our algorithm. Dhaka Univ. J. Sci. 61(1): 13-18, 2013 (January) DOI: http://dx.doi.org/10.3329/dujs.v61i1.15090